An in vitro study to compare glazed and polished surfaces of feldspathic porcelain and comparing three different polishing systems - Aakriti Singh; Bhaskar Sengupta; Harinder Kuckreja; K B. S Kuckreja (Wolters Kluwer Medknow Publications, 2017)
Aim and Objectives: Effective finishing and polishing of dental restorations provides for oral health, function and aesthetics. There are studies which state that porcelain should be glazed after chairside adjustments, whereas, some studies advocate that polishing is equivalent or better than glazing. The main objective of this study was to compare glazing and polishing, and also, to compare three different polishing systems available in the Indian market, namely SHOFU, DFS and DIATECH. Materials and Methods: One hundred twenty six specimens of porcelain discs were prepared and divided into 3 groups with subsequent subgroups. Quantitative analysis was done using a profilometer to determine the roughness quotient (Ra value) and qualitative analysis was done using a Scanning Electron Microscope (SEM). Result: It was found out that glazing produces smoother surfaces as compared to polishing. Among the three different polishing systems used, SHOFU was found to produce the most smooth surfaces. Conclusion: The polished surface provided by the polishing kits was not comparable to the smoothness of the glazed surface and cannot substitute for glazing.